Paclobutrazol effect on plant growth and tomato (Solanum lycopersicum L.) production in protected environment - Seleguini, Alexsander (2016)
The objective was to study, for hybrid AF 7631, the effect of three concentrations of paclobutrazol (0, 50 and 100 mg ai L-1) and two application methods (soaking seeds and seedlings application) on the development of plants, production and fruit quality of tomato in greenhouse in the spring / summer period. The trial was conducted the Finance Teaching, Research and Extension UNESP Ilha Solteira (SP). Application methods and the increase in PBZ concentrations did not significantly alter the productivity, however, the treatment of seedlings, via irrigation, 15 days after sowing, with increasing concentrations of PBZ induced linear reductions in plant height evaluated at 17, 34, 51 and 65 days after transplanting (DAT) in absolute growth rate of height in the range between 17 and 34 DAT at the time of first cluster of insertion and dry weight of leaves and stems. Regardless of PBZ application method, the concentrations significantly reduced the effect of side shoots and increased production of small fruit. The climatic conditions, especially temperature, prevented the expression of the maximum yield potential of the crop.